Sensitivity analysis of airport noise using computer simulation - Flavio Maldonado Bentes; Jules Ghislain Slama (Journal of Aerospace Technology and Management, 2011)
This paper presents the method to analyze the sensitivity of airport noise using computer simulation with the aid of Integrated Noise Model 7.0. The technique serves to support the selection of alternatives to better control aircraft noise, since it helps identify which areas of the noise curves experienced greater variation from changes in aircraft movements at a particular airport.